PENGARUH MOTIVASI KERJA, KOMUNIKASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SMK PGRI 2 GIANYAR - I Kadek Yogi Prastya; Anak Agung Dwi Widyani; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The success and failure of a company is often determined by the important role of its human resources. There are many factors that influence employee performance, including work motivation, work communication and work discipline. Likewise at SMK PGRI 2 Gianyar, work motivation, work communication and work discipline are factors that can influence employee performance. There is attention and findings regarding the problems of work motivation, work communication and work discipline in an effort to improve and improve employee performance in accordance with the aim of this research to determine the influence of work motivation, work communication and work discipline on employee performance at SMK PGRI 2 Gianyar. The population in this study was 32 people. The number of samples in this study was 32 people. The sampling technique used is the census method or saturated sample. Data analysis in this study used Multiple Linear Regression Analysis using the IBM SPSS Statistics 25 application. The results of the study showed that work motivation had a positive and significant effect on employee performance at SMK PGRI 2 Gianyar. Work communication has a positive and significant effect on employee performance at SMK PGRI 2 Gianyar. Work discipline has a positive and significant effect on employee performance at SMK PGRI 2 Gianyar.